Determining the Association Between MSP1/2 Variant and Multiplicity of Infection on Incidence of Severe Malaria in Sudanese Children in Gezira State, Sudan - Abdalla Alsedeeg; Albadawi Abdelbagi Talha; Sanaa Elfatih Hussein; Sana Ibrahim Mohammed; Bakri Yousif M. Nour; Abubakr Ali Elamin Mohamed Ahmed; Yasir Alruwaili; Muharib Alruwaili; Muyassar K. Tarabulsi; Mohammed H. Alruhaili; Samy Selim (Journal of Pure and Applied Microbiology)
The Almanagil province located in Gezira scheme, Gezira state, Sudan, represents a suitable environment for the breeding of malaria-carrying mosquitoes. An estimated 5.9% of Sudanese people suffer from malaria, with 87.6% of cases caused by Plasmodium falciparum and 12.4% by Plasmodium vivax. Clinical manifestation of malaria cases range from mild uncomplicated to severe and fatal complications and the genetic variants and multiplicity of falciparum infection can worsen the manifestations of malaria. The objective of this work is to determine the degree of genetic variation in P. falciparum infection in a high-transmission region of central Sudan by analyzing merozoite surface protein-1 (msp1) and merozoite surface protein-2 (msp2) variations. During the rainy season of 2022, Eighty-nine children with confirmed severe falciparum malaria whom admitted to Almanagil Pediatric Hospital were included in this study. Dry blood spots were used to extract the DNA and amplification of three msp1 and two of msp2 allelic subfamilies, namely K1, RO33 and MAD20 and FC27 and IC/3D7, respectively. The data was analyzed by using SPSS computer program (v 23.0). The three genetic subfamilies of msp1 (K1, RO33 and MAD20) and the two alleles of msp2 (FC27 and IC/3D7) were identified. Msp1 variants represent K1 (64/89, 71.9%), RO33 (56/89, 62.9%) and MAD20 (72/89, 80.9%), while msp2 diversity represents ICI/3D7 (52/89, 58.4%), FC27 (62/89, 69.6%) and ICI/3D7/FC27(33/89, 37.1%). The MAD20 and FC27 showed high genetic diversity among both genes respectively. RO33 allele shows a strong association with severity of falciparum malaria (OR 2.572, P 0.045 ), while the K1 was the lowest risk factor for malaria severity. The allele subfamily K1 and MAD20 of msp1 were associated with hypoglycemia (OR 4.21 and 2.91) respectively. Our study revealed high genetic polymorphisms of msp1 and msp2. Among Central Sudanese children with high MOI of P. falciparum isolates, there was a significant frequency of msp1, a strong association between the K1 allele and hypoglycemia, and a substantial association between the RO33 and MAD20 alleles with the severity of the infection. These findings could help develop malaria control strategies.